Investigation of fentanyl transformation in wastewater treatment plant technologies using non-targeted analysis - Jamie Simpson; Bradley S. Simpson; Cobus Gerber (Journal of Environmental Chemical Engineering, 2025)

Effect of secondary and tertiary wastewater treatment methods on opioids and the subsequent environmental impact of effluent and biosolids - Jamie Simpson; Bradley Scott Simpson; Cobus Gerber (Chemosphere, 2024)

Allometric equations for estimating aboveground biomass carbon in five tree species grown in an intercropping agroforestry system in southern Ontario, Canada - Amir Behzad Bazrgar; Naresh Thevathasan; Andrew Gordon; Jamie Simpson (Agroforestry Systems, 2024)
Allometric equations were developed for estimating aboveground biomass carbon (AGBC) in five tree species grown in a tree-based intercropping system at the University of Guelph Agroforestry Research Station, Guelph, Ontario, Canada. A total of 66 representative trees from five species: red oak ( Quercus rubra ) [n = 12], black walnut ( Juglans nigra ) [n = 16], black locust ( Robinia pseudoacacia ) [n = 10], white ash ( Fraxinus americana ) [n = 15], Norway spruce ( Picea abies ) [n = 13] were selected, harvested and their aboveground biomass and carbon content were quantified. Three commonly used allometric models were used to develop predictive equations. Regression models were developed and parameterized for each tree species and the best are presented based on information criteria (AIC, AICc, and BIC), mean absolute percentage error (MAPE), over/under estimation (MOUE), root mean square error (RMSE), R 2 , and regression coefficients (a, b) of the observed/predicted (OP) linear regression analysis. All equations with diameter at breast height (D) only and D and tree height (H) as the predictor variables fitted the AGBC data well, with R 2 > 97% and RMSE

The role of acoustics within the sensory landscape of coral larval settlement - Josh W. Pysanczyn; Elizabeth A. Williams; Emelie Brodrick; Daniel Robert; Jamie Craggs; Kristen L. Marhaver; Stephen D. Simpson (Frontiers in Marine Science, 2023)
Recruitment of coral larvae on reefs is crucial for individual survival and ecosystem integrity alike. Coral larvae can detect and respond to a wide range of biotic and abiotic cues, including acoustic cues, to locate suitable sites for settlement and metamorphosis. However, the acoustic ecology of coral larvae, including how they perceive auditory cues, remains poorly understood. In this mini-review we consider both ex situ physiology and behavior, and in situ ecological and behavioral studies, to first provide an updated overview of the abiotic and biotic cues used by coral larvae to guide settlement. We then explore in detail the use of acoustic cues and the current literature on behavioral responses to acoustic stimuli. Finally, we discuss gaps in our understanding of the mechanisms by which coral larvae detect acoustic cues, highlighting a novel application of technology to explore these sensory capabilities. We also address how larval phonotaxis, i.e., the ability to orient to a sound cue, can be applied to coral reef conservation. Current research suggests that acoustic cues are likely used at small spatial scales, and that coral larvae may have directional acoustic sensitivity enabling phonotactic behavior. Recruitment of coral larvae on reefs is significantly influenced by habitat-specific soundscape variation and likely affected by anthropogenic disturbance. We propose a novel application of the remote sensing technology, micro-scanning laser Doppler vibrometry (LDV), to quantify the micromechanical responses of putative acoustically sensitive epidermal microstructures. We then highlight the potential for incorporation of acoustic enrichment techniques in coral reef conservation and restoration interventions.

Distinct coral reef habitat communities characterized by environmental DNA metabarcoding - Laurence Dugal; Luke Thomas; Abinaya Meenakshisundaram; Tiffany Simpson; Rose Lines; Jamie Colquhoun; Simon Jarman; Mark Meekan (Coral Reefs, 2023)
Coral reefs are biodiversity hotspots, places of high endemicity and provide essential services to billions of people globally. With increasing threats to these reefs worldwide, there is a need to implement faster, more efficient ways to monitor spatial and temporal patterns of biodiversity. Environmental DNA (eDNA) metabarcoding offers a promising tool to address this issue, as it has revolutionized our ability to monitor biodiversity from complex environmental samples such as seawater. However, the capacity for eDNA to resolve fine scale shifts in community composition across habitats in seascapes is yet to be fully explored. Here, we applied eDNA metabarcoding using the rRNA 18S Universal eukaryote assay to explore differences in community profiles between samples collected from the lagoon and reef slope habitats across more than 170 km of the Ningaloo Coast World Heritage Area in Western Australia. We recovered 2061 amplicon sequence variants that comprised of 401 taxa spanning 14 different metazoan phyla such as cnidarians, poriferans, molluscs, algae, worms, and echinoderms. Our results revealed strong clustering of samples by habitat type across the length of the reef. Community dissimilarity (beta diversity) between samples collected from the reef slope and lagoon habitats was high and was driven largely by a strong rate of spatial turnover, indicating a distinct set of taxa representing each reef zone community. We also detected a strong pattern of isolation by distance within our slope samples, suggesting that communities are spatially stratified across the length of the reef. Despite high connectivity due to regular flushing of the lagoon environment, our results demonstrate that metabarcoding of seawater eDNA from different habitats can resolve fine scale community structure. By generating multi-trophic biodiversity data, our study also provided baseline data for Ningaloo from which future changes can be assessed.

Envisioning a national invasive species information framework - Jamie K. Reaser; Annie Simpson; Gerald F. Guala; Jeffrey T. Morisette; Pam Fuller (Biological Invasions, 2020)
With a view toward creating a national Early Detection and Rapid Response Program (EDRR) program, the United States National Invasive Species Council Management Plan for 2016–2018 calls for a series of assessments of federal EDRR capacities, including the evaluation of “relevant federal information systems to provide the data and other information necessary for risk analyses/horizon scanning, rapid specimen identification, and rapid response planning.” This paper is a response to that directive. We provide an overview of information management needs for enacting EDRR and discuss challenges to meeting these needs. We then review the history of relevant US policy directives for advancing invasive species information systems and provide an overview of federal invasive species information system capacities, including current gaps and inconsistencies. We conclude with a summary of key principles and needs for establishing a national invasive species information framework. Our findings are consistent with earlier studies and, thus, emphasize the need to act on long-recognized needs. As a supplement to this paper, we have cataloged federal invasive species databases and information tools identified through this work.

Historical Processes and Contemporary Anthropogenic Activities Influence Genetic Population Dynamics of Nassau Grouper (Epinephelus striatus) within The Bahamas - Krista D. Sherman; R. Andrew King; Craig P. Dahlgren; Stephen D. Simpson; Jamie R. Stevens; Charles R. Tyler (Frontiers in Marine Science, 2017)

Profiling the Role of Deacylation-Reacylation in the Lymphatic Transport of a Triglyceride-Mimetic Prodrug - Sifei Han; Luojuan Hu; Tim Quach; Jamie S. Simpson; Natalie L. Trevaskis; Christopher J. H. Porter (Pharmaceutical Research, 2015)

Characterization of lipophilic drug binding to rat intestinal fatty acid binding protein - Tony Velkov; Maria L. R. Lim; James Horne; Jamie S. Simpson; Christopher J. H. Porter; Martin J. Scanlon (Molecular and Cellular Biochemistry, 2009)